Valor & honor - Aselford, Terence; Whitener, Barrett, 1960-; Yarsinske, Amy Waters, 1963-; Carney, John T. (Renton, WA : Topics Entertainment, 2004)
Two narratives blending investigative reporting with undercover exploits. No one left behind chronicles the story of Amy Waters Yarsinske's attempts to uncover the whereabouts of the first U.S. pilot shot down during the Persian Gulf War 1. No room for error takes you inside the United States Air Force Special Tactics units, led by Colonel John Carney
No one left behind / Amy Waters Yarsinske -- No room for error / John T. Carney and Benjamin F. Schemmer
Compact discs
Unabridged
"Two audio books, one low price"--Container
No one left behind read by Terence Aselford ; preface read by the author ; No room for error read by Barrett Whitener
Keywords: Speicher, Michael Scott; Persian Gulf War, 1991 -- Aerial operations, American; Fighter pilots -- United States -- Biography; Special forces (Military science) -- United States -- History -- 20th century; Special forces (Military science) -- United States -- History -- 21st century; United States -- History, Military -- 20th century; United States -- History, Military -- 21st century